DIFFERENCES BETWEEN ENGLISH AND UZBEK GRAMMAR - Avgonova Dinora Abdumurod qizi; Urolova Rayxona Jamshid qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the key grammatical differences between English and Uzbek languages. Due to their belonging to different language families—Germanic and Turkic—their morphosyntactic structures differ significantly. The study focuses on distinctions in sentence structure, tense systems, and grammatical expression. Special attention is given to translation challenges arising from these differences. The findings highlight the importance of understanding both languages’ grammatical features to ensure accurate and natural communication.